Sources of Biographical Information on the Members of Catholic Religious Congregations in Lithuania in the Seventeenth–Nineteenth Centuries - Jovaiša, Liudas (Senoji Lietuvos literatūra, 2017)
The paper is devoted to the review and classification of both manuscript and printed historical sources providing a scholar with biographical information on male and female members of Catholic religious congregations of the Latin rite (excluding the abundantly documented and rather well known Jesuits) active in the territory of the (former) Grand Duchy of Lithuania until 1863 when nearly all religious communities were dissolved.Chronologically, the researched biographical material could be divided into two historical periods: the early one, dominated by fragmentary manuscript material, and the subsequent ‘explosion’ of intense and regular printed documentation (from the 1830s to 1863). Essential biographical information is mostly contained in different kinds of registers of the living members of a certain religious community. One type of such databases is a catalogue: compiled regularly or sporadically, it listed members of a certain religious ‘family’ at a certain historical moment. Another important corpus of biographical information is a personal register of the members of a structural unit of a certain religious congregation: it recorded members of a certain province for a longer period of time and was regularly updated. Registers of novices and vows can be considered the third important source of biographical information. The data contained in these three main types of biographical sources can be supplemented (and in some cases even replaced) by the registers of clerical ordinations, the characteristics of students, the acts of the provincial (or conventual) chapter, and the registers of the election of the superiors of religious communities (in the case of the Trinitarians, also by the decrees of visitations acts, and in the case of the Observant Franciscans, by the complaints of the discretes).Biographical information on the deceased members of religious communities contained in liturgical guides and calendars (directorium), in the registers of the deceased, in memorial books, and in the obituaries not just provides a scholar with some important personal data; in some cases, it proves to be the unique source of biographical information that enables reviving a living portrait of a personality with his / her specific character and virtues.From the point of view of both the variety and quantity of the still extant sources of biographical information (and excluding the members of the Society of Jesus), the Observant Franciscan friars could be regarded as the possible champions in the field. The documentary heritage of the Carmelites, Dominicans, and Discalced Trinitarians is also significant, and Conventual Franciscans, Benedictines and Camaldolese hermits should be mentioned as well. Franciscan and Benedictine nuns produced the richest biographical documentation among female religious congregations, while the most elaborated obituaries were composed by the Piarists and the Fathers of the Congregation of Mission.
Keywords: directorium (liturgical guide / calendar); catalogues / registers of the members of a religious congregation; registers of the novices / vows / holy orders; acts of the chapters of a religious community / province; election acts of a superior; decrees of the visitation acts